Early Levothyroxine Treatment for Subclinical Hypothyroidism or Hypothyroxinemia in Pregnancy: The St Carlos Gestational and Thyroid Protocol - Runkle, Isabelle; de Miguel, María Paz; Barabash, Ana; Cuesta, Martin; Diaz, Ángel; Duran, Alejandra; Familiar, Cristina; de la Torre, Nuria García; Herraiz, Miguel Ángel; Izquierdo, Nuria; Diaz, Ángel; Marcuello, Clara; et al. (Frontiers in Endocrinology, 2021)
The optimal maternal levels of thyroid hormones (TH) during the first trimester of gestation have not been established, nor has the ideal moment to initiate levothyroxine treatment (LT) to improve the evolution of gestation and fetal development. Cut-off points for Thyroid-stimulating hormone (TSH) <2.5 µIU/mL and free thyroxine (FT4)>7.5 pg/mL have been recommended. There are no data on whether initiation of LT <9th Gestational Week (GW) can have a favourable impact. Objective: To define the TSH/FT4 percentiles corresponding with 2.5 µIU/mL and 7.5 pg/mL levels, respectively, at GW8 (Study 1), and evaluate the effects of LT before GW9 on gestation evolution, based on a protocol implemented in our center (study 2). Subjects: 2768 consecutive pregnant women attending the first gestational visit from 2013-2014 and 3026 from 2015-2016 were eligible for Study I and 2 respectively. A final 2043 (study 1) and 2069 (study 2) women were assessed in these studies. Results: Study 1: The FT4 level of 7.5 pg/mL corresponds with the 17.9th percentile, a TSH level of 2.5 µIU/mL with the 75.8th. Women with TSH >2.5 µIU/mL had a history of fetal losses more frequently than those <2.5 (OR 2.33 (95%CI): 1.58-3.12), as did those with FT4 <7.5 pg/ml compared to those >7.5 (OR 4.81; 3.25-8.89). Study 2: A total of 1259 women had optimal TSH/FT4 levels (Group 1), 672 (32.4%, Group 2 had suboptimal TSH or T4l, and 138 (6.7%, Group 3) had suboptimal values of both. 393 (58.5%) in Group 2 and 88 (63.8%) in Group 3 started LT before GW9. Mean (SD) GW24 levels were TSH: 1.96 + 1.22 µIU/mL and FT4: 7.07 +1.25 pg/mL. The highest FT4 value was 12.84 pg/mL. The adjusted risk for an adverse event if LT was started early was 0.71 (0.43-0.91) for Group 2 and 0.80 (0.66-0.94) for Group 3, respectively. Conclusions: Early LT in women with suboptimum levels of TSH/FT4 (2.5 µIU/mL /7.5 pg/ml) at or before GW9 is safe and improves gestation progression. These data support the recommendation to adopt these cut-off points for LT initiation, which should be started as early as possible.